Щодо питання перспективи сталого розвитку вітчизняної сфери надрокористування - Matiukha, Volodymyr V.; Suhina, Olena M. (Institute of Industrial Economics of NAS of Ukraine, 2016)
The article is devoted to determination of a role of national mineral raw-material complex in economy of Ukraine and development of proposals on maintenance of its sustainable development in the context of globalization and integration. The urgency of this problem is caused by imperfection of the institutional environment in the national sphere of subsoil use. Sustainable development of the state economy should be implemented due to own mineral resource potential. The purpose of scientific research is the assistance to sustainable development of sphere of the subsoil use of Ukraine by development of offers to perfection of maintenance of the balanced functioning of the mineral raw-material complex. The subject of scientific research is mining attitudes in the national sphere of subsoil use. As to realize the tasks of the research the authors used general scientific theoretical methods including analysis for studying a modern condition and prospects of sustainable development of a mineral raw-material complex of Ukraine, and special methods for economic researches including economic-statistical (for revealing tendencies and laws of development of a mining complex) and prognostic. The novelty of the scientific research is the development of practical recommendations on formation of efficient state policy of effective use of subsoil through its institutional reforming. Sustainable development of economy of Ukraine both in intermediate-term and long-term prospects should be based on own mineral raw-material resources. The current state of the mineral raw-material complex is analyzed and its role in national economy is identified. The technogenic aspect of national sphere of subsoil use is considered as well. The principal causes of irrational use of subsoil and, first of all, the low level of reproduction of domestic mineral raw-material base are identified. Recommendations on the improvement of the system of the state control over the rational use of subsoil at mining and reasonable state mineral raw-material policy at legislative level are offered, which are directed on maintenance of sustainable development of national sphere of the subsoil use in the conditions of processes of globalization and integration.